EVALUASI KESEHATAN POHON MENGGUNAKAN INDIKATOR FOREST HEALTH MONITORING PADA RUANG TERBUKA HIJAU UNIVERSITAS PALANGKA RAYA: Evaluation of Tree Health Using Forest Health Monitoring Indicators in Palangka Raya University Green Space Area - Nuwa; Emirama Waruwu; Eritha Kristiana Firdara; Robby Octavianus; A. Triyadi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
Palangka Raya University Campus is a form of urban Green Open Space (GOS) that hasecological, social, cultural and aesthetic benefits. It is assumed that many trees which arepart of the green open space on the Palangka Raya University campus are experiencingunfavorable conditions. To obtain this information, a study was conducted using the foresthealth monitoring (FHM) method. The purpose of this study was to obtain data on thelevel of tree damage and the form of pests and diseases as well as human disturbance inthe green open space area of Palangka Raya University